ASSIGNMENT DESIGN SHAPES STUDENT LEARNING - Budi Wahyuni, Retno; Kuswardhani, Naniek (Jurnal Pariwisata dan Perhotelan Indonesia, 2015)
Designing a good assignment will shape the student learning. Have we known the mostimportant thing in designing and selecting assignments for our students. Asstated byMaryellen Weimer (2015:2):â€ We can more effectively shape learning outcomes if we startwith objectives that force us to get specific about whatwe want students to know and be ableto.â€Specific coourse objectives should be decided before designing a good assignment that canforce the teacher to find specific assignment matched to what the students have to know andbe able to do, so a teacher can have more effective learning outcomes. Every assignmentinfluences the shape of learning outcomes.In modern era technology a teacher has more options to design writing assignments. Theresearch done is finding the learning outcomes from the students by giving the same writingdesign assignment. The data is taken from comparing their writing through blog or respons toposts that students know, will be read and commented on not only by their peers but also bypublic blog posts, and peer writing that will be read and commented on only by their partner.The result is the students could get a lot of comments that can make them more aware of theirmistakes in writing through blog, while through peer writing the students get comments onlyfrom their partners. In other words, the students could get better outcomes through blog thanpeer writing.Keywords: a good assignment, learning outcomes, objectives